Animal domestication and behavior - Price, Edward O. (Cabi Ser., 2002)
This book synthesizes existing knowledge of the process of domestication and how captive breeding and management of wild and domestic animals have affected their behaviour and other biological traits. The emphasis is on companion animals, farm animals, laboratory animals, including aquaculture species and insects, and animals kept in zoos and wildlife parks. The topics covered are: genetic and experiential contributions to the domestication process, variation under domestication, adaptation to the biological and physical environments, behavioural development in captivity, the adaptation of captive-reared wild and domestic animals when reintroduced into the wild, and the effects of domestication on animal welfare.